2004
DOI: 10.1098/rspb.2004.2730
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasite–modulated deposition of maternal androgens in great tit eggs

Abstract: Maternal yolk androgens can promote growth and competitive abilities of nestling birds but are also suggested to increase susceptibility to parasites or suppress immune function. We tested the hypothesis that females exposed to ectoparasites during egg formation will adjust the content of androgens in the yolk. We predicted that when anticipating high levels of parasitism, females deposit (i) less androgens into all eggs of their clutch and (ii) smaller amounts of androgens in eggs late in the laying sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
109
4
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(129 citation statements)
references
References 35 publications
15
109
4
1
Order By: Relevance
“…Birds hatched from eggs with experimentally elevated yolk testosterone concentrations dispersed over significantly longer distances. Moreover, in a previous study, these authors showed that female great tits transferred lower concentrations of yolk androgens into the eggs when their nest was infested with ectoparasites compared with unexposed control females [192]. These two results suggest that the deposition of low concentrations of yolk androgens into the eggs of nests with parasites might thus be a female strategy to promote philopatry of parasitized offspring and thus to increase her offspring's and thereby her own fitness.…”
Section: Hormonally Mediated Maternal Effects On Dispersal and Populamentioning
confidence: 80%
“…Birds hatched from eggs with experimentally elevated yolk testosterone concentrations dispersed over significantly longer distances. Moreover, in a previous study, these authors showed that female great tits transferred lower concentrations of yolk androgens into the eggs when their nest was infested with ectoparasites compared with unexposed control females [192]. These two results suggest that the deposition of low concentrations of yolk androgens into the eggs of nests with parasites might thus be a female strategy to promote philopatry of parasitized offspring and thus to increase her offspring's and thereby her own fitness.…”
Section: Hormonally Mediated Maternal Effects On Dispersal and Populamentioning
confidence: 80%
“…Even if within-clutch variation in hormone deposition would have occurred in some individuals of our study population, the third egg would still represent the medium concentration of the whole clutch, as long as the pattern of within-clutch variation is linear (as found in many studied species with significant within-clutch variation, e.g. Reed and Vleck, 2001;Groothuis and Schwabl, 2002;Pilz et al, 2003;Tschirren et al, 2004).…”
Section: The Cross-fostering Experimentsmentioning
confidence: 94%
“…In most species studied so far, including the collared flycatcher and its sister species the pied flycatcher (Ficedula hypoleuca), the between-clutch variation in yolk androgen levels is higher than the within-clutch variation (e.g. Reed and Vleck, 2001;Groothuis and Schwabl, 2002;Pilz et al, 2003;Tschirren et al, 2004;Michl et al, 2005;Müller et al, 2007b, Tobler et al, 2007T. Laaksonen, unpubl.…”
Section: The Cross-fostering Experimentsmentioning
confidence: 99%
“…This may result in Table 2 elevated levels of oestradiol in plasma, but not in the yolk of the mature oocyte, since at the time of maximal yolk deposition oestradiol production in that follicle has decreased (Johnson 2002 fig. 1, Tschirren et al 2004). Moreover, comparative analyses of the three yolk androgens in eggs of passerine birds reveal a strong correlation of 5a-DHT with testosterone, but not of testosterone with androstenedione (Schwabl et al 2007).…”
Section: Glucocorticoids and Thyroid Hormonesmentioning
confidence: 97%
“…Yolk testosterone varies with maternal parasite exposure (Tschirren et al 2004;Gil et al 2006) and influences natal dispersal distance (e.g. Tschirren et al 2007), indicating consequences for parasite-host coevolution and population genetics.…”
Section: Introduction (A)mentioning
confidence: 99%